Effects of several establishment modes of Miscanthus × giganteus and Miscanthus sinensis on yields and yield trends. Issue 7 (18th May 2020) - Ouattara, Malick S.; Laurent, Anabelle; Barbu, Corentin; Berthou, Magali; Borujerdi, Elsa; Butier, Arnaud; Malvoisin, Pierre; Romelot, Dominique; Loyce, Chantal
Abstract: Miscanthus is a C4 perennial grass originating from East Asia, the yields of which progressively increase in the first years of growth. Several species for bioenergy have been studied since the mid‐1980s in Europe, in particular ( Miscanthus × giganteus [ M. × giganteus ]), due to its high yields. M. × giganteus is mainly cultivated in France and established from rhizomes. Our study aimed to assess, in field conditions, alternative establishment methods combined with an alternative species, Miscanthus sinensis ( M. sinensis ). We set up a multi‐environment experimental network. On each trial, we tested two treatments with M. × giganteus, established from rhizomes (G_r‐sd) and from plantlets obtained from rhizomes (G_p‐sd), and two treatments with M. sinensis seedlings transplanted in single (S_p‐sd) and double density (S_p‐dd). ANOVA was performed to compare establishment and regrowth rates across treatments, as well as yields across treatments and site‐years. A logistic model was used to describe yield trends and to compare the maximum yield reached and the rate of yield increase of both species. Results showed that miscanthus establishment from plantlets resulted in higher establishment (between 87% and 92%) and regrowth (between 91% and 94%) rates compared to establishment from rhizomes. Treatments with M. × giganteus obtained higher average yields across site‐years than those with M. sinensis, but more variable yields across site‐years. We showed a strong species effect on yields, yield components (shoot weight, shoot density and shoot number per plant) and light interception (through leaf area index). Lastly, to use M. sinensis established from transplanted plantlets as an alternative to M. × giganteus, research would be required on the breeding of M. sinensis sterile seeds to avoid risks of invasiveness. Abstract : Our study aimed to propose alternative establishments of Miscanthus × giganteus ( M. × giganteus ) from rhizomes, which results in high establishment costs and sometimes in a low emergence rate. To achieve that goal, we set up an multi‐environment trial under field conditions exploring seven sites in the North and Center of France during 6 years of growth of Miscanthus. Results showed that Miscanthus sinensis established from transplanted plants could be an alternative to M. × giganteus established from rhizomes because of its lower yield variability across contrasting environments. In addition, the emergence rate from transplanted plants was 10% better than that from rhizomes.